Structure-Function Analysis of Edible Fats - Marangoni, Alejandro G., 1965- (Elsevier Ltd. : Academic Press and AOCS Press, 2018)
Structure-Function Analysis of Edible Fats, Second Edition summarizes the latest approaches in the quantification of the physical structure of fats and its relationship to macroscopic functionality. The book takes a proven, general approach, presenting principles and techniques in a way that can be applied to any lipidic material. As the maturity of the field has increased since the first edition, there is an increased need for more sophisticated quantitative approaches to common problems encountered by industry. This book outlines modern methods used for this purpose by some of the leading authorities in the field today. Edited by expert Alejandro Marangoni, and with contributions from leaders in field, the book features the latest developments, including chapters on Phase Behavior of Fat Mixtures and the Rheology and Mechanical Properties of Fats Methods Used in the Study of the Physical Properties of Fats (including a new section on microscopy).
Keywords: Oils and fats, Edible -- Analysis.; elektronické knihy; electronic books